(untitled) (Scientific journal of the Fergana State University, 2024)
The article provides information about the botanical description of (Echinacea purpurea (L.) Moench) medicinal plant, its geographical distribution, use in folk and modern medicine, and cultivation technology. Preliminary results of research on the development of a scientific and practical basis for growing the medicinal plant E. purpurea have also been obtained. In our experiments, the seeds of the Echinacea purpurea plant were sown manually to a depth of 3-5 cm. Before planting, the seeds were treated with biofertilizers obtained from microorganisms. Seeds were sown in trays measuring 60x30 cm. 3-4 seeds were placed in each nest. It has been proven that when using organic and microbiological fertilizers, it is possible to obtain a large mass from the above-ground parts of the plant - the stem, leaves and flowers, and from the underground parts - the root stem and roots. Since the plant is perennial in its life form, in the first year only underground (root) and aboveground (bunch of leaves) organs were formed; from the second year of the growing season, generative ones (flowers, fruits) appeared.